2021
DOI: 10.1002/mnfr.202000982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Mediterranean Diet or Nut Consumption on Gut Microbiota Composition and Fecal Metabolites and their Relationship with Cardiometabolic Risk Factors

Abstract: Scope To examine whether a Mediterranean Diet (MedDiet) compared to the consumption of nuts in the context of a habitual non‐MedDiet exerts a greater beneficial effect on gut microbiota and fecal metabolites; thus, contributing to explain major benefits on cardiometabolic risk factors. Methods and Results Fifty adults with Metabolic Syndrome are randomized to a controlled, crossover 2‐months dietary‐intervention trial with a 1‐month wash‐out period, following a MedDiet or consuming nuts (50 g day‐1). Microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Our findings are also in line with the recent work by Medawar and colleagues on associations between eating behavior and dietary fiber intake, which suggested that beneficial bacteria belonging to the Ruminococcus genus (poorly represented in cluster C2) correlated with healthier eating behavior [68]. As recently discussed, the tendency of some GM profiles to represent more the altered metabolic phenotype of obesity (such as cluster C2 in our study) could however be related not so much to the consumption of unhealthy foods as to the absence of Ruminococcaceae and Lachnospiraceae families, which are commonly related to beneficial effects on insulin and glucose homeostasis [69,70].…”
Section: Discussionsupporting
confidence: 61%
“…Our findings are also in line with the recent work by Medawar and colleagues on associations between eating behavior and dietary fiber intake, which suggested that beneficial bacteria belonging to the Ruminococcus genus (poorly represented in cluster C2) correlated with healthier eating behavior [68]. As recently discussed, the tendency of some GM profiles to represent more the altered metabolic phenotype of obesity (such as cluster C2 in our study) could however be related not so much to the consumption of unhealthy foods as to the absence of Ruminococcaceae and Lachnospiraceae families, which are commonly related to beneficial effects on insulin and glucose homeostasis [69,70].…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with previous reports, we found that irradiation led to a reduction in vitamins, amino acids, and some minerals in the GF diet (27,28,39). Diets with different nutrient contents lead to differences in the microbiota and metabolic profile of the organism (7,40). In the present study, we observed differences in gut microbiota and serum metabolism in SPF mice due to GF diet.…”
Section: Discussionsupporting
confidence: 92%
“…Diets with different nutrient contents lead to differences in the microbiota and metabolic profile of the organism ( 7 , 40 ). In the present study, we observed differences in gut microbiota and serum metabolism in SPF mice due to GF diet.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that Lachnospiraceae NK4A136 group supplementation was correlated with increased plasma HDL-C concentration and decreased plasma TMAO and liver TC concentrations. Galié et al [ 40 ] also found that a Mediterranean diet increases the relative abundance of the Lachnospiraceae NK4A136 group in faeces, reduces insulin resistance and decreases the risk of cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%